Dominican Republic : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report provides an assessment of accounting, financial reporting and auditing practices within the corporate sector in the Dominican Republic (DR), using International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA) as benchmarks, and drawing on international experience and good practices in those fields. The principal objective of this ROSC assessment is to assist the Government in strengthening private sector accounting and auditing practices, and in enhancing financial transparency in the DR's corporate sector. The development objectives these efforts address are improving the investment climate, fostering competitiveness and furthering regional and international economic integration. Moreover, the recommendations arising from the assessment support the Government's efforts to ensure the stability of the financial sector and mitigate the risk of crises.